Providence, Creation, and Gnosticism According to the Gnostics - Burns, Dylan M. (Journal of early Christian studies, 2016)
So many aspersions have been cast upon the term Gnosticism that even studies about Gnostics prefer to avoid it. Did the Gnostics then teach no Gnosticism? The extant works (mostly from Nag Hammadi) which seem to resemble their thought prefer the language of myth to the concise, syllogistic formulations that would help modern scholars define Gnosticism. However, Gnostic myths are often glossed with the philosophical terminology of their day, particularly regarding the concept of divine care, or providence (p?????a). When set aside contemporary Platonic, Stoic, and early Christian views about providence's activity in creation, it becomes clear that Gnostic myths express a distinctive view that presupposes a disjunction between the creator of the cosmos and the true God, who expresses Its fundamental kinship with human beings through intervention in the creation of terrestrial humanitynot the terrestrial world. Gnostic texts that emphasize instead the ubiquity of God's will in creation seem to attempt to hedge or mitigate this perspective, rather than contradict it. From the standpoint of ancient Greco-Roman philosophy, then, we might say that there certainly was a distinctively Gnostic view about divine providence, inviting us to rehabilitate the term Gnosticism accordingly.